Observer-based fault-tolerant control against sensor failures for fuzzy systems with time delays - Tong, Shaocheng; Yang, Gengjiao; Zhang, Wei (Zielona Góra: Uniwersytet Zielonogórski)
This paper addresses the problems of robust fault estimation and fault-tolerant control for Takagi-Sugeno (T-S) fuzzy systems with time delays and unknown sensor faults. A fuzzy augmented state and fault observer is designed to achieve the system state and sensor fault estimates simultaneously.
Keywords: fuzzy time-delay systems; sensor faults; state observer; fault-tolerant control; linear matrix inequalities; stability analysis